PENGARUH KUALITAS GURU, MODEL PEMBELAJARAN DAN GAYA BELAJAR SISWA TERHADAP PRESTASI BELAJAR SISWA DI ERA MERDEKA (Studi pada SMA Negeri 1 Gandapura Kabupaten Bireuen) - Fadhla, Anna; Idris, Amiruddin (IndOmera, 2023)
Research was conducted on students of SMA Negeri 1 Gandapura, Bireuen Regency to examine several things, namely (a) examining the relationship between teacher quality, learning models and student learning styles, (b) measuring partially and simultaneously the variables of teacher quality, learning models and student learning styles. student learning on student achievement. Research through a survey with a questionnaire instrument. Applying the associative type quantitative method by developing a path model to determine the value of causality, correlation between variables and the contribution of the factors studied. The results showed that 1) there is a causal relationship between teacher quality and learning models in the medium category (0.577), between learning models and student learning styles in the medium category (0.527) and the relationship between student learning styles and teacher quality. in the moderate category (0.302). 2). There is an influence of teacher quality on student achievement of 28.15%, the effect of learning models on student achievement of 27.45% and the influence of student learning styles on student achievement of 30.4%. 3) Simultaneously the quality of teachers, learning models and student learning styles make a significant contribution of 68.8% to student achievement at SMA Negeri 1 Gandapura, Bireuen Regency.